Improving students’ ability to analyze discourse through the moodle-based blended learning method - Noermanzah Noermanzah; Suryadi Suryadi (English Review: Journal of English Education, 2020)
The Covid-19 pandemic period requires online learning in Discourse Analysis Courses that are not bound by place and time by providing interactive activities and supported by complete teaching materials. The learning method is the Moodle-based Blended Learning method. This study aims to describe the results of increasing the ability to analyze discourse through the moodle-based blended learning method in the Master Program of Indonesia Language Education, University of Bengkulu. The research method used is a classroom action research method with the model of Kemmis, McTaggart, & Nixon. Data collection techniques used are tests, observation, interviews, and documentation. The data analysis technique used qualitative data analysis and quantitative data analysis and the determination of the indicators for the success of the action. Test the validity of the data used triangulation of data sources and member check. The results showed an increase in activeness, motivation, independence, and student learning outcomes, especially in analyzing discourse after the application of the moodle-based blended learning method. Increasing active, motivated students and the emergence of independence through synchronous activities used Zoom Cloud Meeting and asynchronous activities through Moodle on the website https://elearning.unib.ac.id/ and assisted by Whatsapp. The increase was seen in learning outcomes in analyzing discourse, especially the ability to analyze the description, interpretation, and explanation of cycle 1 with an average value of 77.3 with the criteria B + increased in cycle 2 of 80.75 with criteria A-.